2011
DOI: 10.1089/scd.2010.0236
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Human Hematopoietic Cells from Umbilical Cord Blood Using Roller Bottles in CO2and CO2-Free Atmosphere

Abstract: In this work, we evaluated the expansion of human hematopoietic stem cells from umbilical cord blood in roller bottles. The Iscove's modified Dulbecco's medium, the Stem Pro 34-SFM medium, and the L-15 Leibovitz's medium for cultures in CO(2)-free atmosphere were assessed. At day 5 of culture, total colony forming unit expansions of 14.44 ± 3.74, 11.20 ± 6.37, and 17.25 ± 3.65-folds were attained, respectively. The expansion reached using L-15 medium in roller bottles was around 10 times higher than that achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…They find that RBs are suitable to culture human umbilical CB MNC in all media notice above. L-15 RB had higher and longer CFC expansion (18.39-fold for 13 days) than other medium and expansion using the L-15 medium in RBs was about 10 times higher than that static control cultures [28].…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…They find that RBs are suitable to culture human umbilical CB MNC in all media notice above. L-15 RB had higher and longer CFC expansion (18.39-fold for 13 days) than other medium and expansion using the L-15 medium in RBs was about 10 times higher than that static control cultures [28].…”
Section: Discussionmentioning
confidence: 81%
“…In another study in 2014, Andrade-Zald ıvar et al had contrary data than 2011 and revealed that maximum total cell proliferation (26 vs. 20-folds for 10 days culture) and maximum progenitor expansion (17 vs. 16-folds for five days culture) in the static medium were higher than RB. These difference are maybe higher progenitor expansion could be found even earlier in the cultures of the enriched fractions and also, primitive cells cultured in static conditions may lose their stem features [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Roller bottles have been used for MSC‐based tissue engineering applications 76,77, and recently for the expansion of hMSCs and hematopoietic cells 78,79. Cohen and McNiece 79 demonstrated enhanced expansion of hMSCs in roller bottles with no significant changes in morphology, but reduced expression of interleukin‐1 and interleukin‐6, compared with those grown in T‐flasks.…”
Section: Bioreactors For the Expansion Of Hmscsmentioning
confidence: 99%
“…Cellmate TM (Bernard et al ., ; Kunitake et al ., ). Very recently, Andrade‐Zaldivar et al ., ) reported a 17‐fold increase in CFU after 8 days of expansion of UCB MNCs using roller bottles (Andrade‐Zaldivar et al ., ).…”
Section: Bioreactor Culture Systemsmentioning
confidence: 99%